The effect of whisker movement on radial distance estimation: a case study in comparative robotics - Evans, Mathew H.; Fox, Charles W.; Lepora, Nathan; Pearson, Martin J.; Sullivan, J. Charles; Prescott, Tony J. (Frontiers in Neurorobotics, 2013)
Whisker movement has been shown to be under active control in certain specialist animals such as rats and mice. Though this whisker movement is well characterised, the role and effect of this movement on subsequent sensing is poorly understood. One method for investigating this phenomena is to generate artificial whisker deflections with robotic hardware under different movement conditions. A limitation of this approach is that assumptions must be made in the design of any artificial whisker actuators, which will impose certain restrictions on the whisker-object interaction. In this paper we present three robotic whisker platforms, each with different mechanical whisker properties and actuation mechanisms. A feature-based classifier is used to simultaneously discriminate radial distance to contact and contact speed for the first time. We show that whisker-object contact speed predictably affects deflection magnitudes, invariant of whisker material or whisker movement trajectory. We propose that rodent whisker control allows the animal to improve sensing accuracy by regulating contact speed induced touch-to-touch variability.